“One Belt One Union” : Cooperation of Russia and China, and Mongolia’s Foreign Policy - Dorjsuren, Munkhjargal (Mongolian Journal of International Affairs, 2021)
The “2015 Joint Statement on Cooperation between Eurasian Economic Union (EAEU) and the Silk Road Projects” signed by Russia and China opened the bilateral cooperation among “Eurasian Economic Union” which consists of Russia, Belarus, Kazakhstan, Armenia, and Kyrgyzstan, and “One Belt One Union” of China (5+1). “One belt One Union” and “Eurasian Economic Union” separately, are the Political projects of Vladimir Putin and Xi Jinping, acting as a new form of cooperative mechanism, and considered to have great impact on regional economic integration. The world is now watching whether these two nations are partners or rivals. For Mongolia, every action and decision made by the “One Belt One Union” is important as it influences our future development. This article intends to identify the cooperation of the two great nations which has major influence on Mongolia, and Mongolia’s foreign policy towards the cooperation.